2010
DOI: 10.1002/mnfr.200900108
|View full text |Cite
|
Sign up to set email alerts
|

Garlic components inhibit angiotensin II‐induced cell‐cycle progression and migration: Involvement of cell‐cycle inhibitor p27Kip1 and mitogen‐activated protein kinase

Abstract: Garlic has been used for prevention and treatment of hypertension; however, the molecular mechanisms of garlic's effects remain to be elucidated. In this study, the mechanisms of the in vitro effect of organosulphur compounds derived from garlic on growth and migration of cultured aortic smooth muscle cells isolated from spontaneously hypertensive rats were investigated. We demonstrated that allyl methyl sulphide (AMS) and diallyl sulphide (DAS) inhibited aortic smooth muscle cell angiotensin II-stimulated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 43 publications
(44 reference statements)
1
29
0
Order By: Relevance
“…Garlic has been reported to exhibit extensive biological activities (Butt et al 2009;Santhosha et al 2013;Suleria et al 2015), including antioxidant (Capasso 2013), antifatigue (Morihara et al 2007), anticancer (Nicastro et al 2015), and antimicrobial (Lanzotti et al 2014) activities. Garlic may also have a positive role in immunonutrition (Nantz et al 2012) and help prevent cardiovascular diseases (Castro et al 2010;Rahman 2007a). The main bioactive components in garlic are organosulfur compounds (Yun et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Garlic has been reported to exhibit extensive biological activities (Butt et al 2009;Santhosha et al 2013;Suleria et al 2015), including antioxidant (Capasso 2013), antifatigue (Morihara et al 2007), anticancer (Nicastro et al 2015), and antimicrobial (Lanzotti et al 2014) activities. Garlic may also have a positive role in immunonutrition (Nantz et al 2012) and help prevent cardiovascular diseases (Castro et al 2010;Rahman 2007a). The main bioactive components in garlic are organosulfur compounds (Yun et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Further, long-term use of dietary garlic may have a protective effect against rise in blood pressure. Castro et al ( 2010 ) demonstrated that allyl methyl sulfi de (AMS) and diallyl sulfi de (DAS) inhibited aortic smooth muscle cell angiotensin II-stimulated cell cycle progression and migration. Their inhibitory effects were associated to the prevention of the cell cycle inhibitor p27(Kip1) (p27) downregulation and the reduction of extracellular signal-regulated kinase 1/2 phosphorylation.…”
Section: In-vitro Studiesmentioning
confidence: 99%
“…The antihypertensive properties of garlic have been linked to stimulation of intracellular nitric oxide and hydrogen sulphide production, and blockage of angiotensin II production, which in turn promote vasodilation and thus reduction in Blood Pressure (Castro et al, 2010). The study was investigated the effect of consumption of garlic powder on blood pressure and renin angiotensin system in a nitric oxide deficiency hypertension model in male rats.…”
Section: Antioxidant Principle Of Garlic:-mentioning
confidence: 99%